2012
DOI: 10.5433/1679-0359.2012v33n4p1515
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the transfer of passive immunity by the analysis of immunoglobulin and serum proteins of Holstein calves

Abstract: This present study evaluated the serum concentrations of the fractional and total proteins, the immunoglobulin concentrations, and the dynamics of passive immune transfer in 25 female Holstein calves. All calves were maintained with their respective dams for 24 hours during which the ingestion of colostrum was done ad libitum. The determinations were done within 24 hours after suckling and at 30 days of age. The gamma fraction of proteins was the predominant immunoglobulin observed 24 hrs after the suckling of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
0
1
1
Order By: Relevance
“…Failure of passive transfer is diagnosed when GGT activity drops below 50 U/L in the first two weeks of life. In our study, GGT activity in the serum of all calves significantly exceeded the levels reported in Holstein calves (167.20 U/L) (Garcia et al, ). In a study presented by Negri Filho et al (), GGT activity levels in Holstein calves 24 hr after birth (399.1 U/L) were similar to those noted in control group (Se0) animals in our study.…”
Section: Discussioncontrasting
confidence: 75%
“…Failure of passive transfer is diagnosed when GGT activity drops below 50 U/L in the first two weeks of life. In our study, GGT activity in the serum of all calves significantly exceeded the levels reported in Holstein calves (167.20 U/L) (Garcia et al, ). In a study presented by Negri Filho et al (), GGT activity levels in Holstein calves 24 hr after birth (399.1 U/L) were similar to those noted in control group (Se0) animals in our study.…”
Section: Discussioncontrasting
confidence: 75%
“…Esta elevação reflete um incremento na capacidade de síntese dessa proteína relacionado à idade (Kaneko 1997) e à ingestão de compostos nitrogenados na dieta (Costa et al 2007). Os valores de gamaglobulinas encontraram-se elevados ao segundo dia de vida (24-36 horas) (Quadro 1) devido a absorção de IgG maternas pelo colostro (Costa et al 2008, Garcia et al 2012, Pires Júnior et al 2013, para após reduzirem seus valores até os 60 dias de idade em ambas as raças. A inversão na relação A:G ocorreu em torno dos 30 dias, sendo o maior valor observado aos 60 dias de vida em ambas as raças estudadas, semelhante ao encontrado por Teixeira et al (2012) em bovinos da raça Crioula Lageana variedade aspada.…”
Section: Quadro 1 Valores Médios E Desvios-padrão (X±s) Da Concentraunclassified